Maximum Strategy for Teachers to Develop Saving Habits in Young Children at Tadika Tinta Khalifa Malaysia Words - Dina Wandira; Alfi Amalia (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2026)
Financial literacy from an early age is an important foundation for shaping children’s future financial behavior and character, particularly through saving habits. This study aims to analyze teachers’ pedagogical strategies in fostering saving habits among early childhood students at Tadika Tinta Khalifah Malaysia, as well as to identify the impacts and the supporting and inhibiting factors in their implementation. This study employed a qualitative approach with a descriptive design. The research subjects included classroom teachers and the school principal, while early childhood students became the objects of observation related to saving behavior. Data were collected through observation, semi-structured interviews, and documentation, and analyzed using the Miles and Huberman interactive model through data reduction, data display, and conclusion drawing. The findings indicate that teachers implemented saving habit strategies through regular hands-on saving activities, the use of creative learning media, and teachers’ role modeling in demonstrating frugal and disciplined behavior aligned with early childhood developmental characteristics. These strategies positively influenced children’s enthusiasm for saving activities, strengthened discipline and responsibility, and improved basic financial literacy, such as understanding the function of money, the purpose of saving, and the difference between needs and wants. The success of these strategies was supported by teachers’ commitment, a supportive school environment, and parental involvement, while limited parental understanding of early financial literacy and differences in family economic backgrounds were identified as inhibiting factors. This study contributes to the development of early childhood financial literacy research by presenting a contextual pedagogical strategy model based on habituation and teacher role modeling within an Islamic preschool setting in Malaysia, and by emphasizing the importance of school–family collaboration in fostering sustainable saving habits from an early age.